Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3892/or.2018.6663
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR‑21 promotes cell apoptosis in oral squamous cell carcinoma by upregulating PTEN

Abstract: MicroRNA‑21 (miR‑21) has been identified as an oncogene and confirmed to serve an important role in carcinogenesis in various types of cancer. However, the effect and mechanism of miR‑21 in oral squamous cell carcinoma (OSCC) has not been fully elucidated. In the present study, miR‑21 inhibitor and empty vector were transfected into OSCC cells, and non‑transfected cells were used as a blank control. The results indicated that when compared with the control and scramble groups, miR‑21 inhibitor suppressed the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The oncogenic potential of miR-21 in oral squamous cell carcinoma (OSCC) cell lines was underlined in relation with PTEN protein levels. Specifically, the induced underexpression of miR-21 correlated with the upregulation of PTEN gene expression and inhibition of cell growth, with these results showing miR-21 to be a potential therapeutic target in OSCC [33]. MiR-21 was also reported as a regulator of the immune response in tongue cancer, playing a role in expressly activating the nuclear factor NF-κB pathway in CAL27 cell line exosomes [34].…”
Section: Discussionmentioning
confidence: 79%
“…The oncogenic potential of miR-21 in oral squamous cell carcinoma (OSCC) cell lines was underlined in relation with PTEN protein levels. Specifically, the induced underexpression of miR-21 correlated with the upregulation of PTEN gene expression and inhibition of cell growth, with these results showing miR-21 to be a potential therapeutic target in OSCC [33]. MiR-21 was also reported as a regulator of the immune response in tongue cancer, playing a role in expressly activating the nuclear factor NF-κB pathway in CAL27 cell line exosomes [34].…”
Section: Discussionmentioning
confidence: 79%
“…In addition, Zheng, Y et al . reported that miR-21 acts as a regulator factor in many signaling pathways such as Wnt/β-catenin and PI3K/Akt 34 . Meanwhile, PTEN is a direct target in downstream of the PI3K/Akt pathway and is associated with apoptosis and tumor growth 35 .…”
Section: Discussionmentioning
confidence: 99%
“…MiR-21 is implicated in the pathogenesis of oral squamous cell carcinoma (OSCC) through its target gene, PTEN. Additionally, the expression of miR-21 and PTEN were associated with the tumors' grade [114]. Tongue squamous cell carcinoma oncomir-21 increased tumors' aggressiveness by inhibiting DKK and consequently activating the Wnt/β-Catenin pathway [115].…”
Section: Mir-21mentioning
confidence: 99%
“…The aforementioned findings shed some light on the implication of miR-21 and its pathogenic pathways implicated in both MetS and cancer. Thus, miR-21 PTEN-induced deregulation is implicated in CRC [103], NSCLC [108], gastric cancer [110], OSCC [114], and cervical cancer [117], being closely correlated with the tumor aggressiveness [110], grade [114], and invasiveness [108]. Additionally, the miR-21/PTEN/PI3K/Akt pathway is implicated in the glucose metabolism and insulin homeostasis [91].…”
Section: Mir-21mentioning
confidence: 99%